2010
DOI: 10.1074/mcp.m900275-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of the Cardiac Myofilament Subproteome Reveals Dynamic Alterations in Phosphatase Subunit Distribution

Abstract: Myofilament proteins are responsible for cardiac contraction. The myofilament subproteome, however, has not been comprehensively analyzed thus far. In the present study, cardiomyocytes were isolated from rodent hearts and stimulated with endothelin-1 and isoproterenol, potent inducers of myofilament protein phosphorylation. Subsequently, cardiomyocytes were “skinned,” and the myofilament subproteome was analyzed using a high mass accuracy ion trap tandem mass spectrometer (LTQ Orbitrap XL) equipped with electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 40 publications
5
75
0
Order By: Relevance
“…24 Media were subjected to mass spectroscopic proteomics analyses as described 25 or used for rat ventricular cardiomyocytes culturing after dialysis in low-serum rat ventricular cardiomyocyte media using Slide-A-Lyzer Dialysis Cassettes (1/100, 3.5 kDa; Thermo Fisher Scientific, Waltham, MA).…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…24 Media were subjected to mass spectroscopic proteomics analyses as described 25 or used for rat ventricular cardiomyocytes culturing after dialysis in low-serum rat ventricular cardiomyocyte media using Slide-A-Lyzer Dialysis Cassettes (1/100, 3.5 kDa; Thermo Fisher Scientific, Waltham, MA).…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…At a depolarizing potential of ؊5 mV, the I Ca,L current density was decreased by 28% after administration of ISO in TG cardiomyocytes. In addition, the ISO-stimulated phosphorylation of phospholamban at Ser 16 was reduced by 27% in TG hearts. Thus, the increased PP2A-B56␣ activity in TG hearts is localized to specific subcellular sites leading to the dephosphorylation of important contractile proteins.…”
mentioning
confidence: 89%
“…co-localized with the myofilaments), but was excluded from the nucleus (15). Analysis of myocardial fractions revealed that B56␣ was decreased in the myofilament fraction and increased in the cytosol after ␤-adrenergic stimulation by isoproterenol (ISO) (16). These dynamic changes in PP2A-B56␣ targeting may contribute to neurohumoral regulation of cardiac performance under physiological conditions and in the diseased heart, as demonstrated for sepsis-associated cardiac dysfunction (17).…”
mentioning
confidence: 99%
“…The major phosphatases controlling thin filament protein phosphorylation are PP1 and PP2A. Both of these phosphatases have been reported to have a Z-disc localization (73,74), placing them in close proximity to the A-and I-band regions of the sarcomere and indicating that their localization may be strain-sensitive. In fact, recent studies (74) indicate that that the B56a unit of the PP2A complex localizes to the Z-disc but moves away with ␤-adrenergic stimulation, whereas light chain 2 phosphatase does not.…”
Section: Dephosphorylation Of Thin Filament Proteinsmentioning
confidence: 99%
“…Both of these phosphatases have been reported to have a Z-disc localization (73,74), placing them in close proximity to the A-and I-band regions of the sarcomere and indicating that their localization may be strain-sensitive. In fact, recent studies (74) indicate that that the B56a unit of the PP2A complex localizes to the Z-disc but moves away with ␤-adrenergic stimulation, whereas light chain 2 phosphatase does not. Our studies (26) showing a decrease in tropomyosin phosphorylation in hearts with constitutively active p38␣ demonstrated co-localization of this MAPK with ␣-actinin at the Z-disc, as well as protein phosphatases (PP2␣ and PP2␤).…”
Section: Dephosphorylation Of Thin Filament Proteinsmentioning
confidence: 99%